2016
DOI: 10.1155/2016/9307064
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Evaluation of Oxidative Stress in Rat Fatty Liver Induced by a Methionine‐ and Choline‐Deficient Diet

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a serious health problem in developed countries. We documented the effects of feeding with a NAFLD-inducing, methionine- and choline-deficient (MCD) diet, for 1–4 weeks on rat liver oxidative stress, with respect to a control diet. Glycogen, neutral lipids, ROS, peroxidated proteins, and SOD2 were investigated using histochemical procedures; ATP, GSH, and TBARS concentrations were investigated by biochemical dosages, and SOD2 expression was investigated by Western Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 75 publications
3
46
1
1
Order By: Relevance
“…Aging has been also associated with a decline of antioxidant defense efficiency, which together with increased ROS production significantly contributes to a manifestation of an oxidative stress state. This in turn can initially disturb enzyme activity through reversible oxidation of thiol groups, but which ultimately can lead to a more profound alteration in biomolecule structure and integrity (Freitas et al, 2016). Consistent with this, overexpression of antioxidant enzymes decreases ROS production and protects DNA from harmful ROS effects, which is associated with a prolonged life span in Drosophila melanogaster (Orr , Sohal, 1994;Schriner et al, 2005).…”
Section: Ros and Agingmentioning
confidence: 84%
“…Aging has been also associated with a decline of antioxidant defense efficiency, which together with increased ROS production significantly contributes to a manifestation of an oxidative stress state. This in turn can initially disturb enzyme activity through reversible oxidation of thiol groups, but which ultimately can lead to a more profound alteration in biomolecule structure and integrity (Freitas et al, 2016). Consistent with this, overexpression of antioxidant enzymes decreases ROS production and protects DNA from harmful ROS effects, which is associated with a prolonged life span in Drosophila melanogaster (Orr , Sohal, 1994;Schriner et al, 2005).…”
Section: Ros and Agingmentioning
confidence: 84%
“…When the oxidative and nitrosative stresses exceed the antioxidant capacity of any body tissue an extensive amount of malondialdehyde (MDA) is generated, intense cellular damage and consequential accelerated apoptosis follows. The overall status affects tissue DNA and membrane phospholipids integrity; resulting in severe tissue injury and/or cell death [ 45 – 47 ]. 8-hydroxylated guanine species such as 8-oxoguanine and 8-hydroxy-2-deoxyguanosine (8-OHDG) are repair products of oxidized guanine lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Methionine ‐ and choline ‐ deficient (MCD) diet is one of the most commonly used dietary models of NAFLD and NASH. Freitas et al () reported that MCD diet increased liver level of MDA and decreased liver levels of SOD and GSH. It also enhanced ROS reaction in the cytoplasm of steatotic hepatocytes and increased immunoreaction of carbonyl protein groups around the lipid droplets.…”
Section: The Role Of Oxidative Stress In Nafld and Nash And The Effecmentioning
confidence: 99%